NEONATAL MARFAN SYNDROME: CLINICAL DESCRIPTION AND COMPLEX APPROACH TO DIAGNOSTICS AND TREATMENT - V. A. Rumyantseva; Yu. A. Rogozhina; N. P. Kotlukova; E. V. Zaklyazminskaya (Российский кардиологический журнал)
Aim. Molecular-genetic tests for neonatal type of Mrfan syndrome make possible to clarify a dignosis in children with multiple phenotype anomalies and to choose correct treatment strategy.Material and methods. Medical-genetic testing and instrumental diagnostics (echo, Doppler, ECG, chest X-rays) made possible to guess the diagnosis of neonatal Marfan syndrome (MS). Direct DNA-diagnostics of MS for these patients including direct Senger-sequencing of the coding plots and neighbouring introne areas of exones 24-32 gene FBN1 completely proved the diagnosis. Results. First time in Russia in two non-relative families with newborns having multiple phenotype anomalies the diagnosis of MS was set at the first year of life and confirmed by molecular-genetic methods.Conclusion. The results of the study must be introduced into practice at specialized pediatric, cardiological and cardiosurgical centres and departments to estimate the risk of sudden death, choose treatment strategy, prescribe gene-specific therapy.